Flight control and landing precision in the nocturnal bee Megalopta is robust to large changes in light intensity - Baird, Emily; Fernandez, Diana C.; Wcislo, William T.; Warrant, Eric J. (Frontiers in Physiology, 2015)
Like its diurnal relatives, Megalopta genalis use visual information to control flight. Unlike their diurnal relatives, however, they do this at extremely low light intensities. Although Megalopta has developed optical specialisations to increase visual sensitivity, theoretical studies suggest that this enhanced sensitivity does not enable them to capture enough light to use visual information to reliably control flight in the rainforest at night. It has been proposed that Megalopta gain extra sensitivity by summing visual information over time. While enhancing the reliability of vision, this strategy would decrease the accuracy with which they can detect image motion - a crucial cue for flight control. Here, we test this temporal summation hypothesis by investigating how Megalopta’s flight control and landing precision is affected by light intensity and compare our findings with the results of similar experiments performed on the diurnal bumblebee Bombus terrestris, to explore the extent to which Megalopta’s adaptations to dim light affect their precision. We find that, unlike Bombus, light intensity does not affect flight and landing precision in Megalopta. Overall, we find little evidence that Megalopta uses a temporal summation strategy in dim light, while we find strong support for the use of this strategy in Bombus.